Diversidade e bioprospecção de fungos endofíticos associados a Stryphnodendron adstringens (Mart.) Coville (Barbatimão - Fabaceae) - Camila Rodrigues de Carvalho (2011)
Endophytic fungi are microorganisms that growth inside plant tissue, with no apparent symptom of disease. These microorganisms are found in differents plants and they can represent a promising source for a variety of bioactive metabolites with great potential for pharmacological use. Stryphnodendron adstringens (Mart.) Coville (Fabaceae) is an angiosperm plant with wide geographical distribution and it is used because of this healing, anti-inflammatory, hemostatic, antimicrobial, antiseptic and antidiarrheal activity. Until now there are no studies regarding its associated endophytic mycota, despite its wide use in popular medicine. The aim of this study is to elucidate this diversity of endophytic fungi diversity associated with S. adstringens and evaluate their production of antifungal, cytotoxic and antiparasitic metabolites. Leaves and stems fragments of thirty young and old individuals of S. adstringens were inoculated on Potato Dextrose Agar (PDA), after surface sterilization. The plates were incubated for a period up to 60 days and the fungi isolates were purified on PDA medium. Two hundred filamentous fungi were obtained from young individuals, and 147 from old individuals. All the isolates were deposited into the Microorganisms and Cells Culture Collection of the Universidade Federal de Minas Gerais. All the isolates were grouped according to their macroscopic characteristics into 99 morphotypes, and one isolate of each group was selected to molecular identification by sequencing the ITS region of the rRNA gene. The isolates identified were belong to the genus: Alternaria, Arthrobotrys, Aspergillus, Botryosphaeria, Cladosporium, Colletotrichum, Coniochaeta, Cytospora, Diaporthe, Fimetariella, Guignardia, Massarina, Muscodor, Neofusicoccum, Nigrospora, Paraconiothyrium, Penicillium, Pestalotiopsis, Phomopsis, Preussia, Pseudofusicoccum, Sordaria, Sporormiella, Trichoderma and Xylaria. All genera belonging to the Ascomycota phylum. Moreover, three taxa were identified as Diaporthales sp., Pezizales sp. and Glomerellaceae sp. The abundance of the taxa ranged from 0,31% to 20,76%. Phomopsis sp., Diaporthe phaseolorum, Diaporthales sp. and Guignardia camelliae were the most abundant. Taxa diversity was measured by Shannon (H) and Simpson indices. The fungal community associated with old plants presented the highest H (H = 2,79), but the Simpson index presented values close between young and old plants (0.90 e 0.88), wich indicates a uniform distribution of taxa into the each community. The endophytic fungi were cultivated in PDA medium during 15 days and after this period, the fungal growth and the medium were treated with ethanol in order to obtain crude extracts. The antifungal activity of these crude extracts was evaluated by the method of microdilution in plate using strains of Candida albicans (ATCC 18804, 2.1A, 15.3C) as target. The toxicity assays to human cancer cell lines were evaluated using the cancer cell lines MCF-7 (breast) and TK-10 (renal). The antiparasitic activity was evaluated with amastigote-like forms of Leishmania amazonensis. At the concentration 100 g/mL, 0.3% of the extracts were considered promising (the extracts presented inhibition values greater than or equal to 70%), 5.2% were moderately promising (the extracts presented inhibition values greater between to 50-69%) and 94.5% unpromissing (the extracts presented inhibition values less than or equal to 70%) against at least one of the C. albicans strains. On the tests with extracts at 250 g/mL, 13.7% of the extracts were promising, 56.8% were moderately promising and 39.5% unpromissing. None of the extracts were active against L. amazonensis and 18.7% fungal extracts were active against the cancer cell lines. The active fungi were identified as: Colletotrichum boninense, Diaporthe phaseolorum, Glomerellaceae sp., Guignardia mangiferae, Nigrospora oryzae, Penicillium sp., Pestalotiopsis clavispora, Phomopsis sp., Pseudofusicoccum sp. and Xylaria sp. The results obtained in this work contributes for the knowledge of the endophytic mycota associated to S. adstringens. The endophytic fungi with active extracts represent a possible potential source for substances that can be used as prototypes to the development of new antimicrobial and antitumor drugs